EXISTENCE SOLUTION FOR NONLINEAR FRACTIONAL DIFFERENTIAL EQUATION BY THE METHOD OF LOWER AND UPPER SOLUTION - Kabare Gitesh, Santosh Shejal (International Journal of Innovations in Engineering Research and Technology, 2022)
In this paper, by the use of lower and upper solutions we prove the existence and Uniqueness of Initial Value Problem containing nonlinear fractional differential equation.